2011
DOI: 10.1002/mus.21819
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrical stimulation on neuromuscular junction morphology in the aging rat tongue

Abstract: INTRODUCTION-Alterations in neuromuscular junction (NMJ) structure in cranial muscles may contribute to age-related deficits in critical sensorimotor actions such as swallowing. Neuromuscular electrical stimulation (NMES) is used in swallowing therapy, but it is unclear how NMJ structure is affected or if NMJ morphology is best measured in two or three dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…Currently, our laboratory is using an animal model to study the underlying changes to the tongue musculature associated with progressive resistance exercise of the tongue [9, 10]. We have shown that tongue exercise induces changes in muscle fiber size and variability in the genioglossus muscle of aged rats that are associated with increased protrusive tongue forces.…”
Section: 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, our laboratory is using an animal model to study the underlying changes to the tongue musculature associated with progressive resistance exercise of the tongue [9, 10]. We have shown that tongue exercise induces changes in muscle fiber size and variability in the genioglossus muscle of aged rats that are associated with increased protrusive tongue forces.…”
Section: 1 Introductionmentioning
confidence: 99%
“…We found that there was a trend toward an increase in muscle fiber size with tongue exercise and a significant increase in muscle fiber size variability with tongue exercise [9]. In addition, we have shown that neuromuscular stimulation results in a reduction in age-related changes to the morphology of the neuromuscular junction in aged rats [10]. In this study we used our previously described animal model to examine changes in neurotrophin levels in the hypoglossal nucleus of rats with both age and exercise.…”
Section: 1 Introductionmentioning
confidence: 99%
“…Age-related changes in GG muscle structure and physiology have been noted in humans and in animal models (11,15,28,45,50,56,67,68,71,75). Exercise may serve as an effective remediation because recent studies have identified increased GG muscle contraction amplitudes with exercise, as measured with electromyography (EMG) (73,83,88).…”
mentioning
confidence: 99%
“…The density of VGCCs at each NMJ was measured through the division of the total number of puncta (based on each grouping stated) over the endplate volumes. Endplate volume was used as this parameter provide a more accurate determination of the VGCC puncta with respect to the three dimensional expansion of the endplate (Johnson & Connor, 2011).…”
Section: Image Acquisition and Analysismentioning
confidence: 99%